Catalyst‐Free Thia‐Michael Addition to α‐Trifluoromethylacrylates for 3D Network Synthesis. Issue 20 (6th March 2023) - Berne, Dimitri; Lemouzy, Sébastien; Guiffrey, Pascale; Caillol, Sylvain; Ladmiral, Vincent; Manoury, Eric; Poli, Rinaldo; Leclerc, Eric
Abstract: Thia‐Michael additions (1, 4‐additions of a thiol to a Michael acceptor) are generally catalyzed by an external Brønsted or Lewis base. A spontaneous (uncatalyzed) Michael addition of thiols to α‐trifluoromethyl acrylates is described, as well as its application to the very efficient preparation of a thermoset. A thorough mechanistic investigation, based on an experimental kinetic study and on DFT calculations, is presented for the addition of arene‐ and alkanethiols to tert‐ butyl trifluoromethyl acrylate in polar aprotic solvents, unveiling a probable solvent‐assisted proton transfer in the rate‐determining step and a considerable lowering of the energy barrier induced by the CF3 group. Abstract : A fast and efficient catalyst‐free thia‐Michael addition onto α‐trifluoromethylacrylates is thoroughly studied through experimental kinetic studies and DFT calculations in order to elucidate its mechanism. An application to a swift preparation of a thermoset is also reported.Catalyst‐Free Thia‐Michael Addition to alpha‐Trifluoromethylacrylates for 3D Network Synthesis (Leclerc, Poli, et al.)